Coexpression of Genetically Engineered 3-Ketoacyl-ACP Synthase III (fabH) and Polyhydroxyalkanoate Synthase (phaC) Genes Leads to Short-Chain-Length-Medium-Chain-Length Polyhydroxyalkanoate Copolymer Production from Glucose in Escherichia coli JM109 - Nomura, Christopher T. (American Society for Microbiology, 2004)
Polyhydroxyalkanoates (PHAs) can be divided into three main types based on the sizes of the monomers incorporated into the polymer. Short-chain-length (SCL) PHAs consist of monomer units of C(3) to C(5), medium-chain-length (MCL) PHAs consist of monomer units of C(6) to C(14), and SCL-MCL PHAs consist of monomers ranging in size from C(4) to C(14). Although previous studies using recombinant Escherichia coli have shown that either SCL or MCL PHA polymers could be produced from glucose, this study presents the first evidence that an SCL-MCL PHA copolymer can be made from glucose in recombinant E. coli. The 3-ketoacyl-acyl carrier protein synthase III gene (fabH) from E. coli was modified by saturation point mutagenesis at the codon encoding amino acid 87 of the FabH protein sequence, and the resulting plasmids were cotransformed with either the pAPAC plasmid, which harbors the Aeromonas caviae PHA synthase gene (phaC), or the pPPAC plasmid, which harbors the Pseudomonas sp. strain 61-3 PHA synthase gene (phaC1), and the abilities of these strains to accumulate PHA from glucose were assessed. It was found that overexpression of several of the mutant fabH genes enabled recombinant E. coli to induce the production of monomers of C(4) to C(10) and subsequently to produce unusual PHA copolymers containing SCL and MCL units. The results indicate that the composition of PHA copolymers may be controlled by the monomer-supplying enzyme and further reinforce the idea that fatty acid biosynthesis may be used to supply monomers for PHA production.